2019
DOI: 10.1186/s12879-019-3694-z
|View full text |Cite
|
Sign up to set email alerts
|

Preventing sexually transmitted and blood borne infections (STBBIs) among sex workers: a critical review of the evidence on determinants and interventions in high-income countries

Abstract: Background Across diverse regions globally, sex workers continue to face a disproportionate burden of HIV and other sexually transmitted and blood borne infections (STBBIs). Evidence suggests that behavioural and biomedical interventions are only moderately successful in reducing STBBIs at the population level, leading to calls for increased structural and community-led interventions. Given that structural approaches to mitigating STBBI risk beyond HIV among sex workers in high-income settings rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 101 publications
1
28
0
3
Order By: Relevance
“…Violence from the state, clients, individuals posing as clients, or intimate partners-together with unlawful arrest, detention, and discrimination-have severe effects on the HIV/STI-related inequities faced by sex workers. Punitive approaches to sex work hinder HIV prevention [84,85], criminalisation, incarceration, and legal restrictions on sex work constrain sex workers' agency and access to safe working conditions. They also elevate HIV/STI exposure through increased violence [29,76,83].…”
Section: Impact Of Violence On Hiv/stismentioning
confidence: 99%
“…Violence from the state, clients, individuals posing as clients, or intimate partners-together with unlawful arrest, detention, and discrimination-have severe effects on the HIV/STI-related inequities faced by sex workers. Punitive approaches to sex work hinder HIV prevention [84,85], criminalisation, incarceration, and legal restrictions on sex work constrain sex workers' agency and access to safe working conditions. They also elevate HIV/STI exposure through increased violence [29,76,83].…”
Section: Impact Of Violence On Hiv/stismentioning
confidence: 99%
“…5 Threats to sexual health can involve individual behaviors, interpersonal and ecological factors that heighten one's exposure to acquiring or transmitting an STI, or a context that compromises volitional control over one's sexuality, sexual behavior, and sexual safety. [5][6][7] The current study is a secondary data analysis that investigates threats to sexual health among women recruited from health clinic in a small US northeastern urban center. Although previous research has recognized the importance of ecological frameworks to understand the complexity of health and health behaviors in marginalized communities, there continues to be a dearth of research that truly utilizes this perspective to gain insight into the multifaceted factors that can concurrently influence threats to sexual health among women.…”
Section: Introductionmentioning
confidence: 99%
“…These three outcomes have been associated with one another, recurrent HIV/STI transmission, other nonsex-based adverse health outcomes, and contextual behaviors that have implications for one's sexual health and autonomy. 6 A history of STIs among women is not only indicative of unprotected sex acts, 7 but in some contexts has also been associated with early childhood sexual trauma, IPV as an adult, and community/society-level detriments. [8][9][10][11] One systematic review found relationships between increased vulnerability to HIV/STI acquisition via decreased condom and oral contraceptive use and women experiencing IPV.…”
Section: Introductionmentioning
confidence: 99%
“…12 Safer work environments in urban Canada, such as working indoors in managed and supported settings, have been associated with reduced violence, less exposure to criminalization, and lower HIV and STI risks. 11 , 13 Conducting sex work in public spaces can be isolating with limited violence protection and reduced access to health and social services, 13 and has been associated with lower enforcement of client condom use. 11 , 13…”
Section: Introductionmentioning
confidence: 99%
“…11 , 13 Conducting sex work in public spaces can be isolating with limited violence protection and reduced access to health and social services, 13 and has been associated with lower enforcement of client condom use. 11 , 13…”
Section: Introductionmentioning
confidence: 99%